An approach to the situation of pulmonary tuberculosis in indigenous communities of Puerto Gaitán, Meta, Colombia - Liliana Sánchez Lerma; Janeth Carrillo Franco; Yennehire Ochoa Bernal; Norton Perez Gutierrez (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: Tuberculosis (TB) is a highly prevalent disease in Colombian indigenous communities of the Orinoquia.  The prevalence and incidence of TB in these communities may be underestimated due to an inadequate detection and treatment, and the lack of reliable information. Objective: To explore the situation of pulmonary tuberculosis in selected indigenous communities of Puerto Gaitan. Materials and Methods: An exploratory cross-sectional study was conducted in indigenous communities of Puerto Gaitan, Meta, Colombia from June 2015 to November 2015. Socio-demographic surveys were applied, and 200 sputum samples from symptomatic patients with respiratory diseases were collected and analyzed with GeneXpert® (real-time polymerase chain reaction, RT-PCR). Results: The surveys showed that the indigenous population is exposed to deteriorating conditions in their quality of life, which expose them to a greater risk of suffering from tuberculosis. Two of the samples analyzed showed to be positive for Mycobacterium tuberculosis 2/191 (1.04%). Conclusions: It is required to implement a differential surveillance system for tuberculosis in indigenous population according to their living conditions, health, and culture, prioritizing a fast and sensitive diagnosis.  Keywords: Tuberculosis, indigenous population, health conditions, polymerase chain reaction (PCR).